Students’ Perception on the Use of Teachers’ Verbal and Nonverbal Immediacy Toward Students’ Motivation - Mayada, Aisya; Addinna, Ainul (Universitas Negeri Padang, 2025)
This study aims to investigate students' perception on the use of teachers' verbal and nonverbal immediacy toward their motivation. This study employed a descriptive quantitative approach. The population of this study was third-grade students at SMA Negeri 1 Nan Sabaris, consisting of 8 classes. Thus, the total population is 240 students. The researcher decided to use cluster random sampling with two classes as a sample of the population, with a total of 60 students. A questionnaire and an interview were selected as the instruments to collect the data. There are two types of questionnaires used: questionnaires for teachers' verbal and nonverbal immediacy and student motivation. The data from each questionnaire comprises 20 closed-ended statements rated on a 4-point Likert Scale. Students' motivation was measured using the ARCS theory of motivation model, which consists of several motivation indicators such as attention, relevance, confidence, and satisfaction. The findings showed that students had very high motivation of verbal and nonverbal immediacy employed by the teachers in the classroom. Therefore, the results of the teachers' immediacy questionnaire showed that the most frequently used verbal immediacy by the teacher was questioning. Meanwhile, the most frequently used nonverbal immediacy by the teacher was body movements.